Hak Sipil dan Politik - Hasan, Muhardi (Jurnal Demokrasi, 2005)
This article will explain the urgency of the maintenance of civil and political rights as objective needs for all people of a country, both domestically and internationally. In addition, this article will also elaborate the determinant factors of the civil and political rights in a country. The determinant factors include the characteristic of a regime holds power in a country, the inclusion of civil and political rights in a constitution and other regulations, the political culture ofÂ  a society, and the aura of international politic in terms f human rights. Kata Kunci: Hak Asasi Manusia, hak sipil, hak politik, demokrasi, warga negara